Stereological and electrophysiological evaluation of autonomic involvement in amyotrophic lateral sclerosis - AKDENİZ, ESRA; İŞAK, BARIŞ (My University, 2022)
© 2022 Elsevier Masson SASObjective: Previous studies have identified autonomic dysfunction in amyotrophic lateral sclerosis (ALS) using mostly neurophysiological techniques. In this study, stereological evaluation of autonomic fibers and sweat glands has been performed to identify structural evidence of autonomic denervation in patients with ALS. Methods: In this study, 29 ALS patients were compared to 29 controls using COMPASS-31 questionnaire, sympathetic skin response (SSR), and heart rate variability (HRV) at rest. From the same cohorts, 20 ALS patients and 15 controls were further evaluated using staining of autonomic nerve fibers and sweat glands in skin biopsies. SSR and resting HRV were repeated in the ALS patient cohort one year later. Results: COMPASS-31 total score, gastrointestinal- and urinary-sub scores were higher in ALS patients than controls (P = 0.004, P = 0.005, and P = 0.049, respectively). In the ALS patient cohort, SSR amplitudes in hands and feet were lower than in controls (P0.05). While there was no change in nerve fibers innervating sweat glands, their density was lower in ALS patients than controls, and semi-quantitative analysis also showed structural damage (P = 0.02 and P = 0.001, respectively). SSR and resting HRV of ALS patients remained stable during the one-year follow-up period (P>0.05). Discussion: Supporting abnormal neurophysiological tests, stereological analysis revealed direct evidence of autonomic denervation in ALS patients. However, the degenerative process in autonomic nerve fibers is relatively slow, compared to the rate of motor neuron degeneration in this condition.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Fizyoloji; Temel Bilimler; Medicine; Internal Medicine Sciences; Neurology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Human Physiology; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; FİZYOLOJİ; KLİNİK NÖROLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; PHYSIOLOGY; CLINICAL NEUROLOGY; Nöroloji (klinik); Fizyoloji (tıbbi); Neurology (clinical); Physiology (medical); Amyotrophic lateral sclerosis; Autonomic nervous system; Heart rate variability; Motor neuron; Skin biopsy; Sympathetic skin response